2023
DOI: 10.1021/jacs.3c03253
|View full text |Cite
|
Sign up to set email alerts
|

Living/Controlled Anionic Polymerization of Glycolide in Fluoroalcohols: Toward Sustainable Bioplastics

Abstract: Ring-opening polymerization (ROP) is a promising approach to accessing well-defined polyesters with superior (bio)­degradability and recyclability. However, the living/controlled polymerization of glycolide (GL), a well-known sustainable monomer derived from carbon monoxide/dioxide, has never been reported due to the extremely low solubility of its polymer in common solvents. Herein, we report the first living/controlled anionic ROP of GL in strong protic fluoroalcohols (FAs), which are conventionally consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The polymerization proceeded faster in DCE than in other solvents used (e.g., THF, acetonitrile and DMF) (Table and Figure S14) probably due to enhanced interaction between the propagation chain end and monomer, as well as between the AA and monomer in DCE. Previously reported studies also observed faster ROP in solvents with low polarity and low hydrogen-bonding ability. The inherent mechanism of the solvent-dependent kinetics is currently under investigation. It should be mentioned that the l -PNMA has low solubility in THF and acetonitrile that precipitation was observed during polymerization, resulting in broad MW distributions (Table and Figure S11b).…”
Section: Resultsmentioning
confidence: 90%
“…The polymerization proceeded faster in DCE than in other solvents used (e.g., THF, acetonitrile and DMF) (Table and Figure S14) probably due to enhanced interaction between the propagation chain end and monomer, as well as between the AA and monomer in DCE. Previously reported studies also observed faster ROP in solvents with low polarity and low hydrogen-bonding ability. The inherent mechanism of the solvent-dependent kinetics is currently under investigation. It should be mentioned that the l -PNMA has low solubility in THF and acetonitrile that precipitation was observed during polymerization, resulting in broad MW distributions (Table and Figure S11b).…”
Section: Resultsmentioning
confidence: 90%
“…Recently, Hadjichristidis and co-workers reported the living/ controlled anionic ROP of glycolide (GL) using strong protic fluoroalcohols (FAs) as (co)solvents, a class of solvents traditionally considered incompatible with anionic polymerization. 542 NMR titration and computational studies revealed that the FAs play a dual role in the process by not only solubilizing the polymeric product but also serving as an activator for the simultaneous activation of the monomer and living chain end without participating in the initiation step. Accordingly, successful synthesis of well-defined poly(glycolic acid) (PGA) with M n up to 55.4 kg mol −1 and Đ < 1.15 was achieved at RT with optimized polymerization conditions ( t Bu-P 2 /TU3 binary catalyst, in 37.5 v/v% hexafluoroisopropanol (HFAB)/toluene).…”
Section: Chain-growth Ring-opening Polymerizationmentioning
confidence: 99%
“…Recently, Hadjichristidis and co-workers reported the living/controlled anionic ROP of glycolide (GL) using strong protic fluoroalcohols (FAs) as (co)­solvents, a class of solvents traditionally considered incompatible with anionic polymerization . NMR titration and computational studies revealed that the FAs play a dual role in the process by not only solubilizing the polymeric product but also serving as an activator for the simultaneous activation of the monomer and living chain end without participating in the initiation step.…”
Section: Emerging Aliphatic Polyestersmentioning
confidence: 99%
“…3,4 Recently, biodegradable polymers derived from hydroxyl carboxylic acids, such as polyglycolic acid (PGA), polylactic acid (PLA) and poly-b-hydroxybutyrate (PHB), have emerged as green alternatives to petroleum-based plastics, which have received considerable attention. [5][6][7][8] Unfortunately, their complete degradation is very sluggish with the release of CO 2 in the natural environment, which not only increases carbon emissions but also squanders valuable carbon resources. 9,10 In this context, chemical recycling of waste biopolymers into useful chemicals/ feedstocks offers attractive access to achieve plastic sustainability.…”
Section: Introductionmentioning
confidence: 99%